DIGITAL TRANSFORMATION IN ENGLISH LANGUAGE TEACHING IN HIGHER EDUCATION (Ustozlar uchun, 2025)
This article explores the impact of digital transformation on English language teaching in higher education. The study examines innovative digital tools, pedagogical strategies, and blended learning approaches. The paper provides insights into how digital technologies enhance student engagement, motivation, and language proficiency in university settings. Key findings highlight the effectiveness of technology integration in improving teaching outcomes and learner autonomy